KEAJEKAN KONSEPTUAL DALAM METAFORA BARU - Bahren Umar Siregar (Masyarakat Linguistik Indonesia, 2014)
The present reserch on metaphors attempts to study (a) to what degree we can determine the conceptual stability of novel metaphors, and (b) whether the level of conventionality of the novel metaphors has an effect on their conceptual stability. Three relatively new metaphors such as Jeruk kok minum jeruk, literally means ‘How come an orange drinks the orange juice’, Cicak lawan buaya or Cicak vs. buaya (Lizard vs. Crocodile) and Bahasa Indonesia sebagai penghela ilmu pengetahuan (The Indonesian language as a carrier of knowledge) and their usage in various online media and websites were selected as data. The research has shown that the conceptual stability of a novel metaphor is determined by frequent use of the metaphor and saliency of its figurative meaning. As the level of conventionality of the metaphor also depends on the frequency of its use, the conventionality, therefore, has an effect on the conceptual stability